2021
DOI: 10.1002/sim.9226
|View full text |Cite
|
Sign up to set email alerts
|

Ratio estimators of intervention effects on event rates in cluster randomized trials

Abstract: We consider five asymptotically unbiased estimators of intervention effects on event rates in non-matched and matched-pair cluster randomized trials, including ratio of mean counts (r 1 ), ratio of mean cluster-level event rates (r 2 ), ratio of event rates (r 3 ), double ratio of counts (r 4 ), and double ratio of event rates (r 5 ).In the absence of an indirect effect, they all estimate the direct effect of the intervention. Otherwise, r 1 , r 2 , and r 3 estimate the total effect, which comprises the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…In Ma et al (2022), we showed that Var ( r l ) = Var ( r l ) for l = 1, 2, 3, 4, and 5. This equality between the variances of the approximately unbiased estimators and asymptotically unbiased estimators also holds for the estimators for matched-pair CRTs.…”
Section: Ratio Estimatorsmentioning
confidence: 96%
See 4 more Smart Citations
“…In Ma et al (2022), we showed that Var ( r l ) = Var ( r l ) for l = 1, 2, 3, 4, and 5. This equality between the variances of the approximately unbiased estimators and asymptotically unbiased estimators also holds for the estimators for matched-pair CRTs.…”
Section: Ratio Estimatorsmentioning
confidence: 96%
“…The contrast of the target and nontarget groups within each cluster reduces the noise arising from heterogeneity between clusters. If there is no indirect effect or only a trivial indirect effect, r 4 is more precise (smaller standard error) and more powerful than r 2 and r 3 when the heterogeneity between clusters is large (Ma et al 2022). If a nontrivial indirect effect is present, the point estimates are not comparable, but the absolute values of the test statistics, | t ( r l )|, for l = 2, 3, or 4 are still comparable in that they all indicate the probability of rejecting the null hypothesis of the target ratio being 1.…”
Section: Ratio Estimatorsmentioning
confidence: 99%
See 3 more Smart Citations